Education in the VUCA world through formation hard and soft skills in students - Iskhakbayeva, T.G.; Analbekova, K.T.; Koshkumbayev, K.T. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The article is devoted to the actual problem of developing the professionalism of future teachers-psychologists through the formation of hard and soft skills. The authors attach great importance to the formation of these skills, calling them a necessity in the modern world. The authors conducted a theoretical analysis of psychological and pedagogical literature on the topic of the study. The article touches on an equally relevant topic, to which they also paid great attention – this is education in the VUCA world. The relationship of the formation of hard and soft skills and adaptation in the VUCA world was carried out, the main components of the world of transformations were determined: Vision, Understanding, Clarity, Agility. To achieve success in each of the components, teachers need to focus on the formation of students' professional skills. The authors conducted a survey among students of the educational program 6B01101 ‒ Pedagogy and Psychology, the basis of the study was the pedagogical faculty of the Karaganda Buketov University. The article presents the results of an empirical study conducted by the authors. The results of the study allowed the authors to conclude that it is necessary to form not only theoretical knowledge, but also practical skills that will contribute to the creation and development of a competitive and competent society of teachers in the modern VUCA world.
Студенттерде hard skills және soft skills қалыптастыру арқылы VUCA әлеміндегі білім
Образование в VUCA мире через формирование жестких и мягких навыков у студентов
Keywords: skill; competence; vision; understanding; clarity; agility; future teachers; VUCA world; professional sphere; theoretical knowledge; practical skills